2000
DOI: 10.1017/s0021859699007248
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sowing date and irrigation on the growth and yield of pinto beans (Phaseolus vulgaris) in a sub-humid temperate environment

Abstract: SUMMARYThe growth and yield of pinto beans (Phaseolus vulgaris L.) cv. Othello in response to a total of six sowing dates (from October to December) and irrigation was examined over two seasons in Canterbury, New Zealand. In 1994\95, two irrigation treatments (nil and full) were combined with two sowing dates (27 October and 24 November). In 1995\96, Othello was examined under two irrigation treatments (nil and full) and four sowing dates (1 November, 15 November, 29 November and 13 December). The total rainfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 9 publications
6
20
0
4
Order By: Relevance
“…2007). The decrease in yield reported for common bean in this study is consistent with other field observations (Nielsen and Nelson 1998, Dapaah et al. 2000, Boutraa and Sanders 2001), but the decrease in yield reported here in mungbean is not consistent with our previous findings (Bourgault et al.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…2007). The decrease in yield reported for common bean in this study is consistent with other field observations (Nielsen and Nelson 1998, Dapaah et al. 2000, Boutraa and Sanders 2001), but the decrease in yield reported here in mungbean is not consistent with our previous findings (Bourgault et al.…”
Section: Discussionsupporting
confidence: 63%
“…Mungbean yields, however, showed the highest yields at the moderate stress level of RDI in 2003 and the severe stress level of RDI in 2004 (Bourgault et al 2007). The decrease in yield reported for common bean in this study is consistent with other field observations (Nielsen and Nelson 1998, Dapaah et al 2000, Boutraa and Sanders 2001, but the decrease in yield reported here in mungbean is not consistent with our previous findings (Bourgault et al 2007) or with findings from other field studies (Angus et al 1983, Muchow 1985a. We are relatively confident, from the conditions in which they have been selected, that the lines tested should exhibit higher drought tolerance than most cultivars of their species.…”
Section: Discussionsupporting
confidence: 53%
“…Thus, time of sowing plays an important role but there is no such information available on pigeon pea for this region, because pigeon pea is less popular in the hilly region. The importance of the sowing date on crop performance is a well established fact (Redden et al 1997;Dapaah et al 2000;Begum et al 2003). Therefore, the present investigation was carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Although Coyne (1965) was not successful with selection for yield or for yield components in common bean, Sarafi (1978) showed that selection was effective in increasing the number of pods/plant with no simultaneous change in the levels of the other yield components and Coyne (1968) recommended this trait for selection for yields. The 'components of yield' approach has been used widely to explain variations in the yield of grain legumes such as peas (Pisum sativum L.) (Nichols et al 1985), field bean (Vicia faba L.) (Husain et al 1988) and Phaseolus vulgaris (Dapaah et al 2000).…”
Section: Introductionmentioning
confidence: 99%